Capital Controls and the Cost of Debt - Andreasen, E (Palgrave Macmillan Ltd., 2019)
Using a panel data set for international corporate bonds and capital account restrictions in advanced and emerging economies, we show that restrictions on capital inflows produce a substantial and economically meaningful increase in corporate bond spreads, with a one-standard-deviation increase in our capital controls index increasing spreads by up to 35 basis points. The effect of capital controls on inflows differs across firms and across countries; the effect is particularly strong for firms that face more restricted access to alternative sources of external financing. Our findings establish a novel channel through which capital controls affect economic outcomes. © 2019, International Monetary Fund.